2004
DOI: 10.2202/1524-5861.1049
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Foreign Direct Investment on Human Development

Abstract: Various studies in the past have examined the effect of foreign direct investment on economic growth of both developed and developing countries. However, research on the influence of foreign direct investment on an expanded conception of socio-economic progress such as human development is absent. In this article, we examine the effect of foreign direct investment on human development (measured by the human development index) for middle and low-income countries for the period from 1975 to 1999 to fill in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
65
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 27 publications
10
65
2
1
Order By: Relevance
“…The researchers provide surveys of the relevant literature and consider both the positive and negative impacts of FDI to the poor -indirectly by growth-enhancing effects, and directly by distributional effects. The majority of the reviewed studies support that FDI may improve poverty rates and income distribution (Agénor, 2003;Sharma and Gani, 2004;MacDonald and Majeed, 2010b;Reiter and Steensma, 2010;Lehnert et al, 2013;Ucal, 2014;Soumaré, 2015). Other studies make points towards FDI having neutral or negative effects on the poor (Stiglitz, 2002;Huang et al, 2010;Gohou and Soumaré, 2012;Groot, 2014;Uttama, 2015;Agénor, 2003).…”
Section: The Role Of Fdi In Poverty Reductionmentioning
confidence: 99%
“…The researchers provide surveys of the relevant literature and consider both the positive and negative impacts of FDI to the poor -indirectly by growth-enhancing effects, and directly by distributional effects. The majority of the reviewed studies support that FDI may improve poverty rates and income distribution (Agénor, 2003;Sharma and Gani, 2004;MacDonald and Majeed, 2010b;Reiter and Steensma, 2010;Lehnert et al, 2013;Ucal, 2014;Soumaré, 2015). Other studies make points towards FDI having neutral or negative effects on the poor (Stiglitz, 2002;Huang et al, 2010;Gohou and Soumaré, 2012;Groot, 2014;Uttama, 2015;Agénor, 2003).…”
Section: The Role Of Fdi In Poverty Reductionmentioning
confidence: 99%
“…In relation to the impact of MNCs on country-level human rights and human development, see e.g. Sharma and Gani (2004) and Kim and Trumbore (2010). iv We refer to Human Rights as defined in the Universal Declaration of Human Rights and other international instruments, among which the International Covenant on Civil and Political Rights and the International Covenant on Economic Social and Cultural Rights.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Nonetheless, some research indicated that foreign investment has a negative effect on women's health 33. Although this result seems to support open economic policies and more foreign investment, researchers have warned that in less developed countries, the efficacy of foreign investment depends on the political capacity of national governments such as their bargaining power and negotiation skills 34. In addition, the country must have an adequate level of human capital, economic stability and well-developed financial market in order to benefit from foreign direct investment 35.…”
Section: Discussionmentioning
confidence: 99%